PENDIDIKAN ISLAM DALAM PERSPEKTIF SOSIO-KULTURAL - Andi Anira (Hunafa: Jurnal Studia Islamika, 2007)
Sociologically, Islamic education and society are closely related. It can be seen from the role of Islamic education in responding to social phenomena and the development of modern teachnology. Based on this, cultrully, life-long education must be developed to realize the needs of scioety in Islamic education. In other words, Islamic education must give a constribution to the life of society since the floursih or the decline of society highly depends on the quality of Islamic education promoted. Kata Kunci: Pendidikan Islam, perspektif sosio-kultural, pendidikan  seumur hidup